Curly leaf 1, a CHD domain-containing protein, regulates leaf development by H3K27me3 modification in rice - Jingyan Yang; Yatong Chen; Xiaowei Sun; Xiaoyue Zhang; Shiyu Wang; Yanpeng Lyu; Yanjuan Hu; Xiaoxue Wang (Crop Journal)
The leaf is a major organ for photosynthesis, and its shape plays an important role in plant development and yield determination in rice (Oryza sativa L.). In this study, an adaxial curled leaf mutant, termed curly leaf 1–1 (cul1-1), was obtained by chemical mutagenesis. The leaf rolling index of the cul1-1 mutant was higher than that of the wild-type, which was caused by the abnormal development of bulliform cells (BCs). We cloned the CUL1 gene by map-based cloning. A nonsense mutation was present in the cul1-1 mutant, converting a tryptophan codon into a stop codon. The CUL1 gene encodes a chromodomain, helicase/ATPase and DNA-binding domain containing protein. Genes related to leaf rolling and BC development, such as ADL1, REL1 and ROC5, were activated by the cul1-1 mutation. The trimethylation of lysine 27 in histone 3 (H3K27me3), but not H3K4me3, at the ADL1, REL1 and ROC5 loci, was reduced in the cul1-1 mutant. High-throughput mRNA sequencing indicated that the cul1-1 mutation caused genome-wide differential gene expression. The differentially expressed genes were classified into a few gene ontology terms and Kyoto encyclopedia of genes and genomes pathways. In the natural population, 22 missense genomic variations in the CUL1 locus were identified, which composed of 7 haplotypes. A haplotype network was also built with haplotype II as the ancestor. The findings revealed that CUL1 is essential for normal leaf development and regulates this process by inhibiting the expression of genes involved in leaf rolling and BC development.